2002
DOI: 10.4049/jimmunol.168.5.2393
|View full text |Cite
|
Sign up to set email alerts
|

Dendritic Cells Transduced with Protein Antigens Induce Cytotoxic Lymphocytes and Elicit Antitumor Immunity

Abstract: Dendritic cell (DC)-based vaccines are being developed for treatment of patients with cancer, in part because DC are potent inducers of CD8+ CTL. DC MHC class I:antigenic peptide complexes that are required for CTL elicitation are most often generated by incubating DC with peptides or by transfecting (or transducing) DC with cDNAs (or viral vectors) that encode protein Ags. The former approach is feasible when MHC class I Ags and relevant peptides are known. The latter approach may be hampered by inefficient D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
107
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 124 publications
(109 citation statements)
references
References 33 publications
1
107
1
Order By: Relevance
“…The same technique was also successfully employed using recombinant TRP2 protein and cultured DC. 33 Our results provide one possible explanation for the lack of efficacy in human clinical studies using peptide-pulsed DC and suggest that antigenloading strategies for DC-based melanoma vaccines need to be optimized. As a clinically more attractive alternative, we also demonstrated that direct injection of recombinant Adenovirus can be as effective as administration with cultured DC provided that the TRP2 aa180-188 peptide epitope is attached to an immunogenic helper protein such as EGFP.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…The same technique was also successfully employed using recombinant TRP2 protein and cultured DC. 33 Our results provide one possible explanation for the lack of efficacy in human clinical studies using peptide-pulsed DC and suggest that antigenloading strategies for DC-based melanoma vaccines need to be optimized. As a clinically more attractive alternative, we also demonstrated that direct injection of recombinant Adenovirus can be as effective as administration with cultured DC provided that the TRP2 aa180-188 peptide epitope is attached to an immunogenic helper protein such as EGFP.…”
Section: Discussionmentioning
confidence: 84%
“…Diverse antigen-loading strategies including synthetic or mixed tumor-derived MHC class I-binding peptides, recombinant or crude tumor cell-derived protein, plasmid DNA, recombinant virus, synthetic or whole tumor-derived RNA, as well as whole tumor cells or tumor cell-derived apoptotic bodies have been evaluated. 10,11,33,34 Currently, the optimal culture protocol and the optimal antigen-loading strategy for DC-based melanoma vaccines are both a matter of intense debate.…”
Section: Discussionmentioning
confidence: 99%
“…This pathway is currently called "cross-presentation" pathway [4,21]. In an attempt to enhance the cellular uptake and promote the cross-presentation pathway in DCs, many investigators perused the recombinant fusion protein or synthetic peptides which contain CPPs tandemly linked to the Ag [7][8][9][10][11][12][13][14]. However the construction of such a recombinant proteins/ peptides are specific for a single Ag, limiting the usefulness of this technology.…”
Section: Discussionmentioning
confidence: 99%
“…Because the Ag uptake by DCs decreases as the cells mature from iDCs to mDCs, most groups have used iDCs to promote Ag capture and uptake [6]. To facilitate the Ag uptake by DCs, arginine-rich cell-penetrating peptides (CPPs) including HIV-TAT, poly-arginine and penetratin (Int) derived from Antennapedia has been applied recently [7][8][9][10]. Kim et al were the first to demonstrate that Ag-specific cytotoxic T lymphocytes (CTLs) are generated in vivo by immunizing mice with DCs that had been exposed to protein-TAT conjugates [7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation